Pengaruh Partisipasi Campaign Berkain Batik di Media Sosial Terhadap Pemahaman Batik Pada Mahasiswa - Icha Haerunnisha; Yeni Sesnawati; Jafar Sodik (Universitas Negeri Jakarta, 2026)
This study aims to examine the effect of participation in the Berkain campaign on social media on students’ understanding of batik. A quantitative approach with a survey method was employed. Data were collected through questionnaires to measure campaign participation and multiple-choice tests based on Bloom’s cognitive taxonomy at levels C1 (knowledge), C2 (understanding), C3 (application), and C4 (analysis) to assess students’ understanding of batik. The research population consisted of students of the Fashion Design Education Study Program at Jakarta State University from the 2022–2025 cohorts. Stratified random sampling was applied, resulting in a total of 163 respondents. Data analysis was conducted using simple linear regression. The results indicate that participation in the campaign shows a positive relationship with students’ understanding of batik; however, the t-test revealed a significance value of 0.064 (Sig. > 0.05), indicating that the effect is not statistically significant. The coefficient of determination (R Square) of 0.021 suggests that campaign participation explains only 2.1% of the variance in students’ understanding of batik, while the remaining variance is influenced by other factors outside the research variables. It can be concluded that although students’ participation in the Berkain campaign on social media is classified as moderate to high, it does not significantly affect their cognitive understanding of batik. Therefore, strengthening batik comprehension within Fashion Design Education courses is necessary. Keywords : batik, fabric campaign, participation, understanding